Draw me a brain: The use of drawing as a tool to examine children's developing knowledge about the “black box” - Brechet, Claire; Blanc, Nathalie; Mortier, Arnaud; Rossi, Sandrine (Frontiers in Psychology, 2022)
Recent studies in neuroeducation underlie the benefits of teaching children about how the brain works. However, very little is known about children’s naïve conceptions about the brain. The current study examined these representations, by asking 6- to 10-year-old children (N = 257) and adults (N = 38) to draw a brain (and a stomach - as a control drawing). The drawings were scored using a content analysis and a list of graphic indicators was derived. First, all the graphic indicators used in the brain drawings were different from those used in the stomach drawings, suggesting that children are able to distinguish these two organs. Second, with age, children depict (i) an increasing number of indicators, (ii) more complex indicators, (iii) indicators that are more anatomically correct, to depict the brain. There is an important evolution between 6 and 10 years-old but also between 10 years-old and adults. These results are discussed in relation to children’s metacognitive knowledge and to their implications for neuroeducation.